Pemanfaatan Teknologi : Strategi Promosi Potensi Desa Melalui Blog Desa - T. Citra Nisa Farza; Della Monica; Suadek Irmawan (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2022)
Efforts to achieve independent welfare for rural communities are closely related to the development of existing village potential. Medium Micro Small Enterprises (MSMEs) and tourism are one of the fastest growing village potentials and contribute to the progress of the village economy. MSMEs in Bekulap Village have the potential to be marketed to a larger segment. However, as the obstacles faced by business actors in general, namely knowledge and management of digital technology which are still not well controlled by MSME actors, lack of capital for business development and others. This activity aims to introduce and promote Bekulap Village outside the region, especially knowing the various economic potentials of Bekulap Village such as MSMEs and online tourism. The methods used are presentations, outreach and case studies. The results of this activity provide public understanding about the importance of using and utilizing digital technology in marketing MSME products which can be increased by conducting education/socialization on the use of blogs.